2013
DOI: 10.5005/jp-journals-10018-1072
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management and Role of Interim Plastic Biliary Stenting in Large and Multiple Pigmented Common Bile Duct Stone

Abstract: Background/Aim: Different endoscopic modalities are available for the extraction of common bile duct (CBD) stones. However, there is no clear consensus on the better therapeutic approach. Aim of the study was to analyze the effectiveness of endoscopic retrograde cholangiopancreatogram (ERCP) and endoscopic sphincterotomy (ES) and the role of 'interim' plastic biliary stent deployment in difficult pigmented CBD stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Additionally, our study found that when the stone number exceeded 2 (mean 2.86±1.46), ERCP alone was insufficient for stone removal. Similar observations were made by Ramakrishnan et al [10,18], who found that stone retrieval may not be possible during the initial procedure when the stone number exceeds 3. In cases where CBD stones cannot be removed using standard methods, temporary plastic stenting may be considered to prevent impaction [19].…”
Section: Results and Observationsupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, our study found that when the stone number exceeded 2 (mean 2.86±1.46), ERCP alone was insufficient for stone removal. Similar observations were made by Ramakrishnan et al [10,18], who found that stone retrieval may not be possible during the initial procedure when the stone number exceeds 3. In cases where CBD stones cannot be removed using standard methods, temporary plastic stenting may be considered to prevent impaction [19].…”
Section: Results and Observationsupporting
confidence: 84%
“…Untreated CBD stones can result in increased morbidity and mortality due to conditions such as obstructive jaundice, recurrent cholangitis, pancreatitis, and secondary biliary cirrhosis. Studies have shown successful removal of CBD stones using standard techniques in a significant proportion of cases, ranging from 78.5% to 86.4% [10,11]. The situation in Bangladesh differs from the global scenario when it comes to the extraction of bile duct stones.…”
Section: Introductionmentioning
confidence: 99%